(untitled) (Energy and Automation, 2025)
Kaplun Viktor Volodymyrovych is a well-known specialist and scientist in the field of energy, has scientific achievements recognized by the domestic and scientific community. He has solved a number of scientific problems that have significant theoretical and practical significance for managing the reliability of electrical complexes based on devices with the shape memory effect, power supply systems with polygeneration, their technological structuring and increasing efficiency through dynamic energy management. During 2010-2011 - Director of the Research Institute of Electric Power Systems of NUBiP of Ukraine, 2011-2019 - Vice-Rector for Scientific and Innovative Activities of KNUTD. Since 2020 - Director of the Educational and Scientific Institute of Power Engineering, Automation and Energy Saving of NUBiP of Ukraine. V. V. Kaplun is one of the founders of the scientific direction and developer of unique technologies for controlling temperature regimes in electrical installations based on shape memory alloys. For the first time, the technologies for producing smart alloys were theoretically substantiated and developed, the characteristics of which exceed world analogues. The products have been implemented in more than 300 enterprises of the energy complex of Ukraine (Kyiv Cable Networks, Zaporizhzhia NPP, Kyivoblenergo, Kharkiv City Electric Networks, Ukrhydronergo, Vinnytsiaoblenergo, Cherkasioblenergo, etc.), Canada (energy company Ontario Hydro). He proposed new theoretical approaches to creating autonomous electromechanical complexes (generator-motor) with compensated asynchronous machines, which provided a significant increase in the energy efficiency of electrical engineering complexes of this class and made it possible to create technological platforms for autonomous power supply systems, which have been implemented in over 140 projects, including 22 facilities of NPP Ukrenergo, Darnytsia, Mostobud PJSC, Eastern Coal Company LLC, the National Space Agency of Ukraine, Roshen PJSC, the State Emergency and Technical Center of the Ministry of Energy of Ukraine, Kyivvodokanal PJSC, etc. A significant contribution of V. V. Kaplun is the development of the theory of optimization of local micro-energy systems based on reliability and cost criteria, which created conditions for the development of principles for the formation of technological structures with polygeneration, balancing models, theoretical and methodological tools for the formation of dynamic energy management systems. Significant results of V.V. Kaplun as an organizer of science is the launch and conduct of the professional accelerator "Energy Security in Wartime" (from 2022), which has become a platform for exchanging experience of business mentors for discussing and solving applied tasks of improving the quality of electricity, reducing losses, managing the reliability of distribution networks, etc., cooperation with stakeholders in the energy sector, promising programs have been formed to increase operational efficiency, an adaptive customer-oriented energy consumption management system ("DTEK Kyiv Regional Networks", "VAP-BUD", Derzhenergonadzor, "Sejm-93", "DTEK Kyiv Electric Networks", "Svitlotek", "Biotestlab", "DTEK Odessa Electric Networks"), the creation of an educational and scientific Digital Energy Cluster with the participation of the National University of Bioresources and Environmental Management of Ukraine, LLC "DTEK Networks", PJSC "Cherkasioblenergo", the Institute of General Energy of the NAS of Ukraine, LLC "482 solutions", the Law Firm Association "Consilium", LLC "Kampov Technology", LLC "Atmosfera", LLC "e-NEXT-Ukraine", which allowed to combine the production and research potential of its participants. Scientific and organizational activities have a wide range of projects: national consultant in the field of energy of the United Nations Development Program in Ukraine in the project "Integration of the provisions of the RIO Conventions into the national policy of Ukraine" (2014-2016), member of the Scientific and Technical Council of the Ministry of Energy of Ukraine (since 2021), member of the working group on the implementation of the Concept of the introduction of "smart grids" in Ukraine by 2035 under the Ministry of Energy of Ukraine (since 2023), member of the Scientific and Methodological Council of the Ministry of Education and Science of Ukraine of the G3 Electrical Engineering subcommittee (since 2024), participant in the working group of the Secretariat of the Cabinet of Ministers on the preparation of Ukraine’s negotiating positions on the conclusion of the Agreement on Ukraine’s Accession to the EU on energy issues (since 2024), vice-president of the Ukrainian Union of Industrialists and Entrepreneurs (since 2020) on issues energy saving and energy efficiency management. He is the head of the international grant projects LIFE22-CET-NS4nZEBs (New Skills for Nearly Zero Energy Buildings), LIFE23-CET-BUSHROSs (Building Up Skills for Home Renovation One-Stop-Shops), ERASMUS-EDU-2022-CB-VET (Vocational Education and Training For Green and Smart Energy in Buildings). Kaplun V.V. is the author of 216 scientific works, including 12 monographs, 3 textbooks and teaching aids, 33 patents and copyright certificates. For his significant contribution to the development of science and education in Ukraine, V.V. Kaplun was awarded the title of "Honored Worker of Science and Technology of Ukraine" (2016), he is a laureate of the State Prize of Ukraine in the field of science and technology (2017), awards Awarded with the Certificate of Honor of the Verkhovna Rada of Ukraine (2020). The editorial board of the journal "Energy and Automation" sincerely congratulates Viktor Volodymyrovych on his anniversary, wishes him good health, and further creative success in his activities.